Prognostic Significance of the Albumin to Fibrinogen Ratio in Peritoneal Dialysis Patients - Xia, Wenkai; Kuang, Meisi; Li, Chenyu; Yao, Xiajuan; Chen, Yan; Lin, Jie; Hu, Hong (Frontiers in Medicine, 2022)
Background Albumin to fibrinogen ratio (AFR) is a demonstrated predictor of mortality in various diseases. The aim of this study was to evaluate the prognostic value of AFR to predict mortality in peritoneal dialysis (PD) patients. Methods We retrospectively analyzed 212 incident PD patients from January 2010 to December 2017 and followed them until December 2019. We used receiver operating curve (ROC) analysis to determine the optimal cut-off point for AFR at baseline to predict overall and cardiovascular mortality during the follow-up period. Kaplan-Meier curve and Cox regression analysis were applied to evaluate the association between AFR and all-cause and cardiovascular mortality. Results The optimal threshold for AFR to predict mortality was 8.48. A low AFR was strongly correlated with worse all-cause and cardiovascular mortality in PD patients. Multivariate analysis revealed that elevated AFR was an independent marker predicting reduced all-cause and cardiovascular mortality (HR 2.41, 95% CI 1.11–5.22, P = 0.026; and HR 2.18, 95% CI 1.21–3.95, P = 0.010, respectively). Conclusions Patients with a high AFR had reduced all-cause and cardiovascular mortality. AFR is a potential prognostic biomarker in PD patients.